Oesophageal atresia: Are "long gap" patients at greater anesthetic risk?. Issue 3 (4th February 2018) - Powell, Laura; Frawley, Jacinta; Crameri, Joe; Teague, Warwick J.; Frawley, Geoff P.
Summary: Background: Long gap oesophageal atresia occurs in approximately 10% of all oesophageal atresia infants and surgical repair is often difficult with significant postoperative complications. Our aim was to describe the perioperative course, morbidity, and early results following repair of long gap oesophageal atresia and to identify factors which may be associated with complications. Methods: This is a single center retrospective cohort study of consecutive patients with oesophageal atresia undergoing surgical repair at The Royal Children's Hospital Melbourne from January 2006 to June 2017. Results: Two hundred and thirty‐nine consecutive oesophageal atresia infants included 44 long gap oesophageal atresia infants and 195 non‐long gap infants. A high rate of prematurity (24.7%), major cardiac (17%), and other surgically relevant malformations (12.6%) was found in both groups. The median age at oesophageal anastomosis surgery was 65.5 days for the long gap group vs 1 day for the oesophageal atresia group (mean difference 56.8 days, 95% CI 48.1‐65.5 days, P  < .01). Surgery for long gap oesophageal atresia included immediate primary anastomosis (n = 10), delayed primary anastomosis (n = 11), oesophageal lengthening techniques (n = 12) and primary oesophageal replacement (n = 6). Long gap oesophageal atresia was not associated with an increased incidence of difficult intubation (OR 2.8, 95% CI 0.6‐22.1, P  = .17), intraoperative hypoxemia (OR 1.6, 95% CI 0.6‐4.5, P  = .32), or hypotension (OR 0.9, 95% CI 0.5‐1.8, P  = .81). The surgical duration (177.7 vs 202.1 minute, mean difference [95% CI], 28 [5.5‐50.4 minutes], P  = .04) and mean duration of postoperative mechanical ventilation (107 vs 199.8 hours, mean difference [95% CI], 91.8 [34.5‐149.1 hours], P  < .01) were shorter for the non‐long gap group. Overall in‐hospital mortality was 7.5% (15.9% long gap vs 5.6% non‐long gap oesophageal atresia OR 1.1, 95% CI 0.4‐3.4, P  = .85). Conclusion: Long gap oesophageal atresia infants have a similar incidence of perioperative complications to other infants with oesophageal atresia. Current surgical approaches to long gap repair, however, are associated with longer anesthetic exposures and require multiple procedures in infancy to achieve oesophageal continuity.